LINDANE AND PROPOXUR RESIDUES IN COCOA FROM CENTRAL REGION OF GHANA (Journal of Science and Technology, 2016)
Lindane and propoxur residue levels in cocoa samples taken from the Central Region of Ghana were determined. Propoxur and Lindane residues in cocoa were extracted by continuous soxhlet extraction with a 1:1 v/v acetone-chloroform and acetone-hexane (20:80 v/v) mixture for pro- poxur and lindane respectively for 12 h. The extracts were passed through preconditioned octa- decyl (C-18) columns to clean up. The pesticides were then analyzed by gas-liquid chromatogra- phy using Flame Ionization Detector (FID) and Electron Capture Detector (ECD) for propoxur and lindane respectively. The concentration range for lindane in cocoa was 0.055 - 3.318 mg/kg. The concentration range for propoxur was 0.001 – 0.991 mg/kg. The mean of lindane in cocoa beans were: 0.411 mg/kg, pod 1.113 mg/kg, testa 0.609 mg/kg , placenta 0.905 mg/kg, leaves 0.892 mg/kg and bark 1.332 mg/kg. The mean concentrations of propoxur in cocoa were: beans 0.235 mg/kg, pod 0.235 mg/kg, placenta 0.276 mg/kg, leaves 0.104 mg/kg, bark 0.491 mg/kg. From the studies it may be preferable to use propoxur for control of pests in cocoa.